A new integrated approach for solving batching, production scheduling and delivery problems in single-stage batch environments - Tibaldo, Aldana; Montagna, Jorge Marcelo; Fumero, Yanina (Computers & Chemical Engineering, 2024)
At operational level, production and distribution integration is very valuable in real-word applications, especially in industries where products must be delivered shortly after production, as in the case of perishable or customized products. Given that the involved decisions belong to different departments and considering their high combinatory, they are usually decoupled. Although this sequential approach simplifies decision making, it can lead to suboptimal solutions for the integrated problem. This paper presents a novel mixed-integer linear programming (MILP) model to simultaneously manage batching, production, and distribution decisions. An efficient strategy is proposed, where feasible routes that vehicles can travel are generated beforehand, which greatly simplify the formulation. Thus, infeasible routes are not considered (reduction of the search space) and several important decisions are made simultaneously when selecting a route (allocation and sequencing of the customers). The performance of this approach is superior to previous ones, especially in large problems.
Keywords: MILP model; Production; Distribution; Operational integration; Routes generation